Supporting trans-national access to key nuclear research infrastructures – OFFERR and JRC OASIS: two complementary projects – One goal - Toulemonde Charles; Seibert Alice; Colineau Eric; Fontana Christiano F.; Nilsson Karl-Fredrik; Raison Philippe; Aldave de las Heras Laura; Boboridis Konstantinos; Eloirdi Rachel; Marabeau Gwladys; Martin Ramos Manuel; Gaillot Stéphane; et al. (EPJ Nuclear Sciences & Technologies, 2025)
The OFFER and OASIS projects both provide transnational access to key nuclear research infrastructures. Since September 2022, the OFFERR project, funded by Horizon Europe/Euratom, supports the SNETP Association by providing R&D experts access to key nuclear research infrastructures across Europe. It addresses financial and logistical barriers that hinder nuclear research by offering a platform for financial support and access to more than 230 experimental facilities. Researchers can submit applications through the OFFERR Call Platform, ensuring eligible projects receive necessary funding and access. This initiative aims to accelerate innovation in nuclear energy by bridging the gap between research ideas and advanced facilities, adhering to EU regulations and fostering international collaboration. The OASIS project is funded by an Administrative Arrangement between the Directorate General for Research and Innovation (DG RTD) and JRC since February 2020 and aims at enhancing open access to JRC's nuclear facilities (11 out of 16 are opened) and the associated technical support. So in the OASIS project, JRC makes available its nuclear research infrastructures to external users free of charge while DG RTD provides their financial support to eligible users to cover their travel and subsistence costs. This allows an optimal use of JRC's unique facilities and nuclear materials not available to European scientists at their home institutions and results in scientific excellence in research that could otherwise not be performed. With a large participation of students and young scientists, OASIS also contributes to the training of the next generation of European scientists in various nuclear fields. Whereas the two projects have one goal, they follow complementary approaches.